Assesment of Antioxidant Activity Test of Kersen Leaf (The phenolic.) and Epiphyte with DPPH (2.2-Diphenyl-1-Picrylhidrazyl) - Nurlutfiyyah Aini; Nita Parisa; Fatmawati (Archives of The Medicine and Case Reports, 2020)
Antioxidant is very important to give protection against free radical activity and highly reactive molecules that could lead in slowing the progression of degenerative disease. In case of degenerative disease, internal antioxidant cannot neutralize the increasing concentration of free radical. Because of that, human needs external antioxidant. Kersen (Muntingia calabura L.) is a plant that is known for its antioxidant content. Plants containing antioxidant experience is kersen (Muntingia calabura L.). Research study to determine the antioxidant activity of Kersen plant and knows the difference of antioxidant activity, based on the process of extract and infusion. Research was done by experimental study which was oriented in testing antioxidant activity in (Morinda citrifolia L.) extract and infusion. Extraction was done by using 96% ethanol as solvent meanwhile infusion was made by using aquadest. Extract and infusion were divided into group of concentration and antioxidant activity was tested by DPPH(2,2-Diphenyl-1-Picrylhidrazyl) method by measuring the absorbance using spectrophotometer at 520 nm wavelength. Percentage of DPPH inhibition and IC50 then analyze d using linear regression analysis. Ethanolic extract of kersen leaf and epiphyte had IC50 value of 113,801 ppm and 98,7802 ppm, respectively. Kersen leaf infusion showed 191,7624 ppm IC50 values, besides its epiphyte had 131,6750 ppm. Antioxidant activity of Muntingia calabura L. in the order from kersen leaf an epiphyte and epiphyte extract has a higher antioxidant content than others.